Prevalence study of arrhythmia in dogs affected for mitral valve disease - Rosa, Laura Jardim; Lanzi, Thaís Duran; Romão, Luciene Maria Martinello [UNESP]; Romão, Felipe Gazza (Editora da Universidade Federal Rural do Semi-Arido - EdUFERSA, 2019)
The mitral valve disease is considered more common heart disease between dogs, and occurs mostly in geriatric and small size dogs. The most affected breeds are, Poodle, Pinscher, Yorkshire Terrier, Fox Terrier, among others. The general signs related to heart disease are cough, tachypnea and lethargy. Another common disorder is arrhythmia, basically related to origin or conduction alterations of electric impulses. Both disorders can be associated in the same patient, which makes necessary the realization of complementary tests for earlier diagnosis and placement of appropriate therapy for the dog, such as, chest radiography, electrocardiogram and echocardiogram. The aim of this paper was to observe, by means of cases retrospective study, the relationship between mitral valve disease and different cardiac rhythms. It was possible observe that alterations in cardiac rhythms are closely linked with activating of neurohormonal compensatory mechanisms of organism due to cardiac remodeling caused for mitral valve disease.
Keywords: Canines; Cardiac remodeling; Endocardiosis; Heart disease